1995
DOI: 10.1074/jbc.270.38.22514
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis of Chromatin on Nondenaturing Agarose Gels Containing Mg2+

Abstract: We show that nondenaturing agarose gels can be used for the study of the structure and dynamic properties of native (uncross-linked) chromatin. In gels containing 1.7 mM Mg 2؉ , chicken erythrocyte chromatin fragments having from about 6 to 50 nucleosomes produce well defined bands. These bands have an electrophoretic mobility that decreases only slightly with molecular weight. This surprising behavior is not observed in low ionic strength gels. Fragments with less than 6 nucleosomes and low content of histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The stacking of nucleosome cores in secondary helices is also in agreement with cross-linking (41) and electron microscopy (19,42,43) results demonstrating that histone octamers can associate, forming different oligomers of higher molecular mass and aggregated helical tubes. The stabilization given by these interactions could be responsible for the folding and selfassembly of chromatin fragments containing few nucleosomes found in electrophoretic studies (2). In our models the first turn is sealed when the fourth (Figure 1E), fifth (Figure 1G), sixth (Figures 1A,F and 2A), or seventh (Figure 1H) nucleosome interacts with the first nucleosome.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The stacking of nucleosome cores in secondary helices is also in agreement with cross-linking (41) and electron microscopy (19,42,43) results demonstrating that histone octamers can associate, forming different oligomers of higher molecular mass and aggregated helical tubes. The stabilization given by these interactions could be responsible for the folding and selfassembly of chromatin fragments containing few nucleosomes found in electrophoretic studies (2). In our models the first turn is sealed when the fourth (Figure 1E), fifth (Figure 1G), sixth (Figures 1A,F and 2A), or seventh (Figure 1H) nucleosome interacts with the first nucleosome.…”
mentioning
confidence: 51%
“…Early work performed with space-filling models built to scale showed us that, to construct a helix of nucleosomes that (i) must be very compact (1) and (ii) has to be initiated and stabilized with a basic element containing about 6 nucleosomes (2), it is necessary to interdigitate the nucleosomes of the successive helical turns. Compact helices, with a small pitch, can be constructed using a relatively large number of nucleosomes per turn, but we have excluded this possibility because these helices require more than 6 nucleosomes to be initiated.…”
mentioning
confidence: 99%
“…To check the properties of chromatin aggregation (condensation) of the various linker histones, we used an MMTV LTR polynucleosome core template of a defined length of 1.3 kbp, which is organized in six phased nucleosomes (24) after reconstitution with liver core histones, as described under "Experimental Procedures." Bartolomé et al (41) showed that about six nucleosomes are sufficient to produce compact structures, such as chromatin fragments, of higher molecular weight, and many other laboratories using different techniques reported results concerning the association of oligonucleosomes to form higher order structures (42,43). Therefore, our model consisting of chromatin fragments containing six nucleosomes is suitable for studying the influence of linker histones on the formation of the polynucleosome complex.…”
Section: Resultsmentioning
confidence: 99%
“…They differ significantly in how the linker DNA is arranged within the condensed chromatin fiber. In the solenoid model, the linker DNA is bent such that the consecutive nucleosomes interact with each other and form a helix (10)(11)(12)(13)(14); in the zig-zag model, the linker DNA remains straight and crosses the fiber axis so that the consecutive nucleosomes appear at the opposite side of the fiber axis (5,(15)(16)(17)(18).…”
mentioning
confidence: 99%